Role of yoga in prevention and management of lifestyle disorders - Ananda Balayogi Bhavanani (Wolters Kluwer Medknow Publications, 2017)
The modern world is facing a pandemic of lifestyle disorders that require changes to be made consciously by individuals themselves, and as yoga is the best lifestyle ever designed, it has potential in the prevention, management, and rehabilitation of prevalent lifestyle disorders. Yogic lifestyle, yogic diet, yogic attitudes, and various yogic practices help humans to strengthen themselves and develop positive health, thus enabling them to withstand stress better. This yogic "health insurance" is achieved by normalizing the perception of stress, optimizing the reaction to it, and by releasing the pent-up stress effectively through various yogic practices. This review paper summarizes important findings of a recent research on yoga in lifestyle disorders including a series of studies at Puducherry, India, documenting positive effects. The majority of studies on yoga and cardiovascular and metabolic health show positive trends and this augurs well for the future of health care in general and the use of yoga as a part of integrative health care in particular. Major benefits of yoga may occur due to its lifestyle components (healthy diet, activity, relaxation, and positive attitude) as well as psychosomatic harmonizing effects of pranayama and yogic relaxation. Yoga places a great importance on a proper and healthy lifestyle whose main components are achar (healthy activities), vichar (healthy relationships), vichar (healthy thoughts), ahar (healthy food), and vihar (healthy recreation). The basic yogic principles useful in the management of lifestyle disorders are discussed including psychological reconditioning and development of appropriate attitudes; stress management normalization of metabolism; and relaxation, visualization, and contemplative practices.